2021
DOI: 10.1186/s12865-021-00425-9
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-related nutritional status in patients with common variable immunodeficiency: association with oxidative stress and atherosclerosis risk

Abstract: Background Common variable immunodeficiency (CVID) is an inborn errors of immunity, that leads to recurrent chronic infections and autoimmune/ inflammatory diseases and neoplasms. It is considered that these condition is related to persistent this immune-inflammatory stimulation and increased oxidative stress. A positive impact on the survival of patients with an inborn error of immunity was observed with advanced clinical care protocols, thus raising concerns about the risk of developing other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Among them, the role of selenium deficiency in the occurrence of cardiovascular diseases has received the most extensive attention [ 48 ]. Se deficiency has been identified as a common cause of vascular disease, with significantly reduced blood Se content observed in patients with chronic vascular diseases compared to healthy individuals [ 49 ].The reduced production of GSH-PX and SOD mediated by Se deficiency, as well as a significant decrease in enzyme activity, leads to intense lipid peroxidation, which impairs cell membrane fluidity and repair and mediates vascular endothelial cell damage [ 50 ]. However, dietary intake is the only way for the body to absorb Se, so Se content can regulate Sel expression in the body [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the role of selenium deficiency in the occurrence of cardiovascular diseases has received the most extensive attention [ 48 ]. Se deficiency has been identified as a common cause of vascular disease, with significantly reduced blood Se content observed in patients with chronic vascular diseases compared to healthy individuals [ 49 ].The reduced production of GSH-PX and SOD mediated by Se deficiency, as well as a significant decrease in enzyme activity, leads to intense lipid peroxidation, which impairs cell membrane fluidity and repair and mediates vascular endothelial cell damage [ 50 ]. However, dietary intake is the only way for the body to absorb Se, so Se content can regulate Sel expression in the body [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Andrade et al. reported decreased levels of ApoA-I associated with increased oxidative stress in 32 CVID patients ( 39 ). MacPherson et al.…”
Section: Low Levels Of High-density Lipoprotein In Cvid: Potential Co...mentioning
confidence: 99%
“…Other evidence of increased oxidative stress in CVID comes from the study of Aukrust et al, where a significantly higher level of reduced homocysteine was found in CVID patients compared to the control group [ 237 ]. A recent study showed how selenium median levels and glutathione peroxidase (GPX) activity were significantly lower in CVID patients compared to controls [ 238 ]. Furthermore, there was a higher percentage of high values of C-reactive protein, higher concentrations of oxidized LDL, and lower concentrations of Apolipoprotein A in the group of CVID patients compared to the control group [ 238 ].…”
Section: Pediatrics Syndromes Associated With Oxidative Stressmentioning
confidence: 99%
“…A recent study showed how selenium median levels and glutathione peroxidase (GPX) activity were significantly lower in CVID patients compared to controls [ 238 ]. Furthermore, there was a higher percentage of high values of C-reactive protein, higher concentrations of oxidized LDL, and lower concentrations of Apolipoprotein A in the group of CVID patients compared to the control group [ 238 ]. All these data suggest increased oxidative stress and cardiovascular risk in these patients [ 238 , 239 ].…”
Section: Pediatrics Syndromes Associated With Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation